2013
DOI: 10.1007/s00262-013-1395-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of tumour infiltrating immune cells in oropharyngeal tumours in comparison to other subsites: relationship to peripheral immunity

Abstract: The level of immune cell infiltration in head and neck squamous cell carcinoma appears to be subsite dependent residing primarily in the stroma and is likely to be dependent on the peripheral immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
6
23
0
Order By: Relevance
“…Lau et al [26] and Green et al [35] have observed a positive correlation between peripheral CD4+ CD25 high Tregs and tumor infiltrating CD4+ CD25 high Tregs in HNSCC patients. In contrast, Wamsom et al [32] who compared CD4+, CD8+, CD4+/CD8+, and FoxP3 T cell subsets have not found any correlation of the levels of these T cells types in the peripheral blood and in the tumor microenvironment between HPV-positive and HPV-negative head and neck tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lau et al [26] and Green et al [35] have observed a positive correlation between peripheral CD4+ CD25 high Tregs and tumor infiltrating CD4+ CD25 high Tregs in HNSCC patients. In contrast, Wamsom et al [32] who compared CD4+, CD8+, CD4+/CD8+, and FoxP3 T cell subsets have not found any correlation of the levels of these T cells types in the peripheral blood and in the tumor microenvironment between HPV-positive and HPV-negative head and neck tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A worse prognosis of HNSCC patients with elevated levels of Tregs in the peripheral blood in comparison with normal Tregs levels patients has been documented in a study [34]. In some reports, a positive correlation of the Tregs levels in the peripheral blood and tumor tissue has been reported [20, 26, 32, 35]. …”
Section: Introductionmentioning
confidence: 94%
“…In regards to HNSCC, various immune subsets have been correlated with clinical outcome (39,40), but the majority of these reports either focused exclusively on HPV + HNSCC or did not distinguish patient populations based on the HPV status. However, high-throughput analyses revealed that HPV + and HPV -HNSCCs are two distinct clinical entities, which have specific molecular features and an altered immune phenotype characterized by CD8 + T cell infiltration (40).…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal squamous cell carcinomas, which arise from the squamous epithelium associated with the lymphoid tissue of the tonsils and base of tongue, have higher numbers of infiltrating iTILs and sTILs compared with other sub-sites [227]. The pre-existing background lymphoid stroma will clearly complicate TIL assessment in these tumors, and an approach similar to that used to assess metastatic deposits in lymph nodes is recommended, that is, to discount any established lymphoid stroma and focus on iTILs in this setting if no desmoplastic stroma is present.…”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%